DIALEKTIKA AL-QUR'AN DENGAN POLA PIKIR KEBERAGAMAAN MASYARAKAT ARAB: Analisis Psiko-Sosial - Syamsul Wathani (IAIN Surakarta, 2016)
This article discusses the mindset of Arab society towards religion which is answered and it was changed after the Koran came. This relationship is dialectic, the Arab community as khitab al-Qur’an. The approach used by the social history of social psychoanalysis. With this approach, this article found some important conclusions. (1) Social history emphasizes that geographic factors, psychological, and social culture have shaped their social siko. Psycho-social impact on their perspectives on God and Religion. God was related to a god (dewa) who can help the biological necessities of life, although not psychologically soothing. As the unsound of the psico-social condition, the way they understand the religions is not correct. They profess religion, somehow does not feel the presence of God. The more they worship Gods, the more discrepancies, social injustices, and tyranny happen. Responding to that matter, the Quran apply persuasive method as the advice (al-din al-nasihah), and discussion (jidal) as their way of thought on religion. (2) The Qur'an came alter their patterns of psychological evolution, from an-nafs al-ammara as bi-su’ society into an-nafs al-lawwamah, until in the end, they had a quiet soul (an-nafs al-Mutmainnah)